2004
DOI: 10.2174/1389450043345308
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines in Neuroinflammation and Alzheimers Disease

Abstract: Inflammation has been reported in numerous neurodegenerative disorders such as Parkinson's disease, stroke and Alzheimer's disease (AD). In AD, the inflammatory response is mainly located to the vicinity of amyloid plaques. Cytokines, such as Interleukin-1 (IL-1), Interleukin-6 (IL-6), Tumor Necrosis Factor alpha (TNF-alpha) and Transforminng Growth Factor beta (TGF-beta) have been clearly involved in this inflammatory process. Although their expression is induced by the presence of amyloid-beta peptide, these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
139
0
4

Year Published

2005
2005
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(144 citation statements)
references
References 0 publications
1
139
0
4
Order By: Relevance
“…Because of the role of IL-6 in osteoclastogenesis (the formation of cells that function in the breakdown and resorption of bone tissue), an increased production of IL-6, as a consequence of the estrogen-depleted menopausal state, contributes to the increased resporption of bone which leads to osteoporosis . Recently, it has become clear that an overall increase in cytokine production, including TNFa, also increases the incidence of osteoporosis and other inflammatory conditions such as cardiovascular diseases and Alzheimer's disease (Pacifici, 1996;Ammann et al, 1997;Cacquevel et al, 2004). From in vitro studies it was found that estrogens can block DNA binding of NF-kB to kB site promoters (Stein and Yang, 1995;Galien and Garcia, 1997;An et al, 1999).…”
Section: Cross-talk Between Nf-jb and The Ermentioning
confidence: 99%
“…Because of the role of IL-6 in osteoclastogenesis (the formation of cells that function in the breakdown and resorption of bone tissue), an increased production of IL-6, as a consequence of the estrogen-depleted menopausal state, contributes to the increased resporption of bone which leads to osteoporosis . Recently, it has become clear that an overall increase in cytokine production, including TNFa, also increases the incidence of osteoporosis and other inflammatory conditions such as cardiovascular diseases and Alzheimer's disease (Pacifici, 1996;Ammann et al, 1997;Cacquevel et al, 2004). From in vitro studies it was found that estrogens can block DNA binding of NF-kB to kB site promoters (Stein and Yang, 1995;Galien and Garcia, 1997;An et al, 1999).…”
Section: Cross-talk Between Nf-jb and The Ermentioning
confidence: 99%
“…Tumor necrosis factor (TNF)-α, a pleiotropic cytokine that exerts a variety of effects, such as growth promotion, growth inhibition, angiogenesis, cytotoxicity, inflammation, and immunomodulation [1], has been implicated in several inflammatory conditions [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Interleukin 6 (IL-6) and interferon alpha (IFN-α) are two pro-inflammatory cytokines that play important roles during chronic inflammation (Sehgal 1990;Ershler 1993;Feghali and Wright 1997;Cacquevel et al 2004). Interestingly, IL-6 and IFN-α exert opposite effects on blood vessel formation; IL-6 is angiogenic (Campbell et al 1993), while IFN-α is angiostatic (Sidky and Borden 1987;Folkman and Ingber 1992).…”
Section: Introductionmentioning
confidence: 99%